1997
DOI: 10.1002/(sici)1097-4644(19971215)67:4<478::aid-jcb6>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Identification of extractable growth factors from small intestinal submucosa

Abstract: When implanted as a biomaterial for tissue replacement, selected submucosal layers of porcine small intestine induce site-specific tissue remodeling. Small intestinal submucosa (SIS), as isolated, is primarily an acellular extracellular matrix material. In an attempt to discover the components of small intestinal submucosa which are able to induce this tissue remodeling, the material was extracted and extracts were tested for the ability to stimulate Swiss 3T3 fibroblasts to synthesize DNA and proliferate. Eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
241
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 540 publications
(245 citation statements)
references
References 37 publications
3
241
0
1
Order By: Relevance
“…SIS is mainly composed of collagen type 1 and contains endogenous growth factors such as FGF and TGF-b and other chemoattractants. [17][18][19] Several studies have shown that SIS can provide a collagenous matrix to promote cell migration into the healing site to enhance revascularization and repair. [20][21][22][23][24] It is hypothesized that SIS enhance and promote the healing of the ACL.…”
Section: Introductionmentioning
confidence: 99%
“…SIS is mainly composed of collagen type 1 and contains endogenous growth factors such as FGF and TGF-b and other chemoattractants. [17][18][19] Several studies have shown that SIS can provide a collagenous matrix to promote cell migration into the healing site to enhance revascularization and repair. [20][21][22][23][24] It is hypothesized that SIS enhance and promote the healing of the ACL.…”
Section: Introductionmentioning
confidence: 99%
“…29 As the SIS contains bioactive agents including growth factors and fibronectin, 24 such chemoattractants could be responsible for the observed increase in neo-tissue formation in the SIS-treated PT defects to enhance the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, SIS contains a variety of growth factors capable of attracting healing cells through chemotaxis. 24 Further, SIS allows cellular infiltration only through its abluminal side, and thus, can prevent adhesion formation on its luminal side. 25,26 When a single layer of SIS was applied to a gap injury of the rabbit medial collateral ligament (MCL), the healing ligament had better collagen fiber alignment with larger collagen fibril diameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics make SIS attractive for tissue regeneration in an unseeded fashion. 14,15 This result was recognized by Lantz and colleagues, who first used SIS in animal studies as a vascular patch, where it demonstrated tissue-specific regeneration in both arteries and veins. 16,17 Kropp and colleagues subsequently demonstrated, in both small and large animal models, that SIS alone can promote bladder regeneration when used as an unseeded graft.…”
Section: Unseeded Technologymentioning
confidence: 99%